MENINGKATKAN KREATIVITAS MATEMATIS SISWA MELALUI PEMBELAJARAN PETA PIKIRAN - Anggita Maharani (Universitas Islam Nusantara, 2016)
Learning Mathematics should be given to all children as a foundation for logical thinking, analytical, systematic, critical, andcreative, as well as the ability to cooperate. Creativity is essentially a person's ability to give birth to something new in the formof ideas and real work in the form of new works as well as a combination of things that already exist. Creativity in mathematicsknown as creative thinking. Learning Mind Map is a learning technique that utilizes the entire record of the brain by usingvisual images and other graphical infrastructure to form an impression of the more interesting so that students can describe theconcept of a material with their own creativity in terms of both language and symbols. Through the Mind Map, we can see theoverall picture of the material we are studying, activates the whole brain works to develop and plan the direction of mind maps,solve a problem by making a creative breakthrough, it is easier to remember the information in a clear and easy to understand, and get something fun and creative.